Signification Analysis of 1984 Movie Poster - Nailla Salsabilah; Ahmad Juma Khatib Nur Ali (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
Movie posters function as promotional media that convey messages through verbal and visual signs. This research aims to identify the verbal and visual signs found in 1984 movie posters and analyze their meanings based on Ferdinand de Saussure's semiotic theory. The data of this research were obtained from the official 1984 movie poster published on IMDb. This research employed a descriptive qualitative method using documentation as the data collection technique. Ferdinand de Saussure's theory on signification through the association between the signifier and the signified was utilized in analyzing the data. Regarding the findings, the movie poster comprises of three verbal symbols like: headline, title, and baseline as well as five visual symbols which include: Big Brother’s face, man and woman, color, typography and layout. These symbols possess certain meanings with regard to dictatorship, surveillance, oppression, rebellion and social control respectively. Thus, the movie poster 1984 acts not only as an advertising tool but also conveys the ideology of the movie.